Energizing management through innovation and entrepreneurship European research and practice - Terziovski, Mile (Routledge studies in innovation, organization and technology ;, 2009)
This volume makes a significant contribution to management knowledge by combining interdisciplinary studies that will collectively provide new knowledge in the field of innovation and entrepreneurship.